Improving Productivity of an Upland Rice and Maize System: Farmer Cropping Choices Or Researcher Cropping Pattern Trapezoids? - Fujisaka, Sam (Cambridge University Press, 1991)
Cropping systems research to improve the productivity of an acid upland rice and maize-based farming system is described and evaluations by co-operating farmers are presented. Farmers rejected introduced patterns. The cropping choices of non-cooperating farmers are described in terms of cost–benefits and the reasons underlying their decisions. An approach that combines an understanding of farmers' systems in order to conduct focused research on the weak points of such systems, together with an evaluation of farmer technology and adaptation, may be more effective than researcher-designed, farmer-implemented cropping pattern trials.